Therapy-related myelodysplastic syndrome/acute leukemia after multiple myeloma in the era of novel agents - Gertz, M.A.; Terpos, E.; Dispenzieri, A.; Kumar, S.; Shah, R.A.; Orlowski, R.; Kastritis, E.; Dimopoulos, M.A.; Shah, J. (Leukemia and Lymphoma, 2015)
Survival for patients with multiple myeloma has increased. Both melphalan and lenalidomide are associated with subsequent development of myelodysplasia. We reviewed the cases of all patients with multiple myeloma who had subsequent development of myelodysplastic syndrome (MDS) or acute non-lymphoblastic leukemia (ANLL) during a 12-year period in three centers. Of 55 patients identified, two received only lenalidomide before myelodysplasia developed. The median time between the diagnoses of multiple myeloma and MDS/ANLL was 52.7 months. Median survival after the diagnosis of MDS or ANLL was 6.7 months. Treatment of MDS comprised allogeneic stem cell transplant in eight patients (median survival, 219 days; one patient alive at 624 days) and a hypomethylating agent in 21 patients (response of stable or better in five patients). Myelodysplasia remains a devastating complication of therapy for multiple myeloma, with short survival and poor response rates to available modalities. © 2014 Informa UK, Ltd.
Keywords: Acute leukemia; Hypomethylating agents; Lenalidomide; multiple myeloma; Myelodysplasia; Stem cell transplant